臺灣南科考古遺址群出土長牡蠣貝殼穩定同位素所反映的全新世中晚期古環境 - 阮孟靈; Nguyen, Manh-Linh (2019)
none To reconstruct Mid-Late Holocene environmental condition in the southwestern Taiwan, stable oxygen and carbon isotopes of 59 Archaeological Pacific oyster shells Crassostrea gigas were studied. In ascending order, specimens were collected from Dabenkeng (5000-4200 yr BP; N=9), Niuchouzi (4200-3300 yr BP; N=10), Dahu (3300-1800 yr BP; N=10), Niaosong (1800-500 yr BP; N = 10), Siraya (500-300 yr BP; N = 10), and Han Chinese (300 yr BP - present; N = 10) cultural components. Carbonate powder was micro-drilled from the ligament area surface along the grow direction then analyzed for its stable isotope compositions. Mean 18O values of oyster shell collected from Dabenkeng, Niuchouzi and Dahu cultures are -6.4±1.4‰ (1; N=98), -6.3±1.2‰ (1; N=37), -6.8 ± 1.0‰ (1; N=115) respectively and they are around 3.5‰ less than that of modern specimens (-3.1±1.2‰; Chen, 2016). It increased 1.1‰ to Niaosong culture (-5.5±1.3‰) and continued raising to -3.7±1.8‰ at Siraya culture. There is no significant difference in average 18O values between Siraya and Han Chinese oyster shells. 18O values indicate that climate condition was nearly stable during Neolithic Age (5000-1800 yr BP) and warmer/wetter than present. It was followed by the general decreasing trend of temperature/precipitation to Siraya culture then was similar to modern climate since Han Chinese culture. Average 13C value of Dabenkeng oyster shells is -3.7±0.9‰. The average 13C values increased 2.7‰ from Dabenkeng to Niuchouzi (-1.0±1.4‰) culture, then continued increasing to -0.4±0.6‰ during the Dahu culture. There was a decrease of 2.5‰ to Niaosong culture (-2.9±0.7‰) that was follow by no significant variation in mean 13C values between Niaosong and Siraya culture. From Siraya to Han Chinese culture, average 13C value decreased 1.9‰. Variation of 13C values since 5000 years may be related to regional productivity and/or type of vegetation change. Based on 18O profiles of each archaeological oyster shell, most of specimens were gathered in the ...